(untitled) (World Bulletin of Public Health, 2026)
The chronic administration of non-steroidal anti-inflammatory drugs dictates a complex physiological compromise between prostaglandin-mediated mucosal defense and endothelial prostacyclin suppression. This study evaluates the precise clinical, gastrointestinal, and renal hemodynamic outcomes of utilizing highly selective cyclooxygenase-2 inhibitors compared to traditional non-selective agents buffered with proton pump inhibitors. A prospective observational cohort study was conducted involving 156 adult patients diagnosed with active, chronic osteoarthritis requiring daily systemic pharmacotherapy. Subjects were stratified into two clinical pathways: a conventional cohort (n=75) receiving continuous diclofenac coupled with omeprazole, and a targeted modern cohort (n=81) receiving isolated celecoxib therapy adjusted for baseline cardiovascular risk. Clinical data indicate that the constitutive suppression of cyclooxygenase-1 generates persistent microvascular ischemia in the gastric mucosa, despite profound acid suppression. The conventional cohort demonstrated a 22.6% incidence of subclinical erosive gastropathy and a mean hemoglobin drop of 1.2 ± 0.3 g/dL by day 90. Conversely, the targeted celecoxib group exhibited an 88.5% reduction in endoscopically confirmed mucosal lesions while maintaining equivalent pain suppression metrics. The selective inhibition of endothelial cyclooxygenase-2 in the targeted group, however, precipitated a subtle but statistically significant elevation in systolic blood pressure by an average of 4.5 ± 1.2 mmHg (p = 0.021), directly correlating with transient sodium retention and mild glomerular filtration rate depression. The dynamics of the observed results suggest that the universal prescription of any single anti-inflammatory class remains physiologically flawed. Comprehensive pharmacotherapy must actively integrate individualized baseline risk stratifications—balancing inherent gastrointestinal vulnerability against silent renovascular rigidity—to achieve sustained musculoskeletal analgesia without inducing iatrogenic organ failure.